Evaluation of Rhododendron luteum and Rhododendron ponticum in pulp and paper production : Procjena mogućnosti uporabe biljaka Rhododendron luteum i Rhododendron ponticum kao sirovine za proizvodnju celuloze i papira - Birinci, Emre (Array, 2020)
In this study, Rhododendron luteum and Rhododendron ponticum were evaluated as raw material for pulp and paper production. 12 different sodium borohydride (NaBH4) added cooking trials were performed for each sample and kraft method was used for pulp production. Pulp properties, such as yield, kappa number and viscosity, and physical properties, such as breaking length and burst index, were determined for each trial. Besides, the effects of active alkali and NaBH4 on the pulp and paper properties were also examined. Optimum cooking conditions were obtained by using 18 % active alkali for NaBH4-free cooking experiments and 0.5 % NaBH4 and 18 % active alkali for NaBH4-added cooking experiments. In NaBH4-added pulping condition, the screened yield, kappa number and viscosity of R. luteum were found to be 43.4 %, 40.1 and 949 cm3/g1, respectively. The respective values for R. ponticum were 41.9 %, 44.5 and 885 cm3/g1. The screened yields of R. luteum and R. ponticum increased by about 2.8 % and 5.3 %, respectively, with 5 % addition of NaBH4 compared to NaBH4-free cooking experiments. Furthermore, with the addition of NaBH4, the kappa numbers decreased while the viscosity increased. The physical properties of the produced papers were also improved by using NaBH4 in cooking liquor. According to the obtained results, it was found that R. luteum and R. ponticum species can be evaluated for pulp and paper production.